The extratemporal lobe epilepsies in the epilepsy monitoring unit - Deepa Dash; Manjari Tripathi (Annals of Indian Academy of Neurology, 2014)
Extratemporal lobe epilepsies (ETLE) are characterized by the epileptogenic foci outside the temporal lobe. They have a wide spectrum of semiological presentation depending upon the site of origin. They can arise from frontal, parietal, occipital lobes and from hypothalamic hamartoma. We discuss in this review the semiology of different types of ETLE encountered in the epilepsy monitoring unit.